Pengembangan Diri Anak Usia Sekolah yang Broken Home: Kontribusi Keluarga dan Guru - Mega Adyna Movitaria (Journal on Education, 2023)
The background of this study is that there is still a widespread negative perception among the general public about children born into broken homes. The general public still believes that children from broken-home families are wild and cannot be cared for. The purpose of this study is to address the issue of how school-age children from broken-home families perceive themselves, especially school-age children with an age range of 7-17 years. This research uses a qualitative case study approach—details of data collection methods through interviews and observations. The subjects of this study were 15 broken home-schooling children. This research shows that parents (mother/father) and other relatives (grandfather, grandmother, aunt, uncle) play a role in children's daily lives. The results of this study can package and represent the contribution of parents and teachers in building the self-concept of broken home children.